2018
DOI: 10.18502/kls.v4i5.2570
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Sleep Quality and Perceived Fatigue Among Nurses at the Cibinong Regional Public Hospital, 2017

Abstract: Fatigue is a critical issue for nurses that may lead to medical errors, degradation in performance, decreased mental acuity and social problems. Poor sleep quality is also a contributing factor in fatigue that nurses experience. Shift work and high workloads are two factors that caused poor sleep quality of nurses. The aim of the present study was to investigate the relationship between sleep quality and perceived fatigue among nurses at the Cibinong Regional Public Hospital, Bogor District. Cross-sectional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…Empirical research has examined fatigue associated with nurses’ job characteristics ( Zhou & Fang, 2015 ), quality of sleep ( Rizky, 2018 ), psychosocial factors ( Alsharari, 2019 ; Rahman et al, 2016 ), job conditions, occupational stress, emotional intelligence ( Huang et al, 2019 ), and recovery in 12-h dayshifts ( Clendon & Gibbons, 2015 ). Other studies have reported the adverse effects of night shift work on the physiological status of nurses, including anxiety, musculoskeletal disorders, stress, development of obesity due to poor eating habits ( Books et al, 2020 ; Liu et al, 2018 ), fatigue, family problems, and decreased job and life satisfaction ( Abdulah et al, 2020 ).…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Empirical research has examined fatigue associated with nurses’ job characteristics ( Zhou & Fang, 2015 ), quality of sleep ( Rizky, 2018 ), psychosocial factors ( Alsharari, 2019 ; Rahman et al, 2016 ), job conditions, occupational stress, emotional intelligence ( Huang et al, 2019 ), and recovery in 12-h dayshifts ( Clendon & Gibbons, 2015 ). Other studies have reported the adverse effects of night shift work on the physiological status of nurses, including anxiety, musculoskeletal disorders, stress, development of obesity due to poor eating habits ( Books et al, 2020 ; Liu et al, 2018 ), fatigue, family problems, and decreased job and life satisfaction ( Abdulah et al, 2020 ).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Hence, occupational fatigue has become a significant risk factor for nurses working in hospitals. Nurses’ fatigue results in mood changes, reduced mental acuity, social problems, degradation in performance and work capability, physical pain, risk of needle stick injuries, musculoskeletal disorders, and medication errors ( Alahmadi & Alharbi, 2018 ; Rizky, 2018 ; Steege & Rainbow, 2017 ). In addition, Hensley et al (2017) found that extended work hours, sleepiness, and fatigue resulted in self-reported clinical errors (23.6%) and near misses (39.4%) in inpatient care among nurses and midwives.…”
Section: Introductionmentioning
confidence: 99%
“…This It is in accordance with the nurse's irregular work schedule, hence, it can disrupt sleep patterns which cause the occurrence of work fatigue for nurses (Allo et al, 2020). With poor sleep quality, it is reluctant to cause risk of 2098 times higher to experience fatigue (Rizky, 2018). It can be overcome by enhancing the quality of sleep by utilizing free time to rest (Kuswana, 2014).…”
Section: Highmentioning
confidence: 99%
“…Workers performing job on night shifts, rarely possess optimal sleep quality. Poor sleep quality increases the risk of 2098 times higher experiencing fatigue (Rizky, 2018). Another factor in the occurrence of fatigue in nurses is mental workload (Ardiyanti, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Zhang et al (2016) reported that more than 70% of nurses in Shanghai, China, had poor sleep quality, stress, and "rotating shift work-related symptoms." A study conducted among nurses at Cibinong Regional Public Hospital showed that 57% had poor sleep quality (Rizky & Hendra, 2018). Compromised sleep quality may increase the risk of poor psychological wellbeing and decrease quality of life (Musa et al, 2018).…”
Section: Introductionmentioning
confidence: 99%